2006
DOI: 10.1182/blood-2006-06-030494
|View full text |Cite
|
Sign up to set email alerts
|

MALT lymphoma and extranodal diffuse large B-cell lymphoma are targeted by aberrant somatic hypermutation

Abstract: Recently, a novel mechanism introducing genetic instability, termed aberrant somatic hypermutation (ASHM), has been described in diffuse large B-cell lymphoma. To further investigate whether ASHM also occurs in mucosa-associated lymphoid tissue type (MALT) lymphoma, we studied the mutation profile of PIM1, IntroductionExtranodal marginal zone B-cell lymphoma of the mucosaassociated lymphoid tissue type (MALT lymphoma) preferentially arises in the gastrointestinal tract, especially the stomach where it is clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 21 publications
3
43
0
Order By: Relevance
“…On the basis of their oncogenic potential, the Pim kinase family is emerging as an important new target for drug discovery (46). However, malignant transformation of lymphoid and myeloid cells involves the dysregulation or mutation of genes including PI3K/Akt pathway and Pim family (14,47). The Akt and Pim kinases produce parallel oncogenic signals and share many molecular targets normally involved in regulating the cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of their oncogenic potential, the Pim kinase family is emerging as an important new target for drug discovery (46). However, malignant transformation of lymphoid and myeloid cells involves the dysregulation or mutation of genes including PI3K/Akt pathway and Pim family (14,47). The Akt and Pim kinases produce parallel oncogenic signals and share many molecular targets normally involved in regulating the cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation of lymphoid and myeloid cells involves the dysregulation or mutation of genes including PI3K/AKT pathway and Pim families that are normally involved in regulating the proliferation and survival of hematopoietic cells (Pasqualucci et al, 2001;Amaravadi and Thompson, 2005;Deutsch et al, 2007;Horn et al, 2008). These altered genes cooperate to endow the transformed cells with cytokine-independent growth.…”
Section: Discussionmentioning
confidence: 99%
“…138 Finally, there is little dispute that t(3;14) is prevalent in a subset of DLBCLs, with extranodal presentation and having the activated B cell-like (ABC) expression profile. 135,137,152 Although the precise frequencies of transition of the various low-grade MZBCLs into DLBCLs are not clear in literature, ample evidence exists that MZBCLs can transform particularly into ABC-type DLBCLs rather than into GC-type DLBCLs: (i) trisomy 3 has been observed as a characteristic alteration in both MZBCLs and ABCtype DLBCLs; 49,51,153 (ii) MZBCLs with high nuclear FOX-P1 were documented to progress into ABC-type DLBCLs; 138 (iii) the majority of genomic alterations in t(11;18)-negative MZBCLs are also found in ABC-type DLBCLs; 49,153 (iv) both MZBCLs and ABC-type DLBCLs are characterized by constitutive NF-κB signaling; 154,155 (v) DLBCLs which still contain a low-grade lymphoma component are mostly of the ABC type; 156 (vi) primary gastrointestinal DLBCLs show a similar expression profile as gastrointestinal MALT lymphoma; 157 and (vii) the majority of rheumatoid arthritis-associated DLBCLs are of the ABC type. 158 The molecular mechanisms underlying MZBCL progression are as yet ill-defined.…”
Section: Genetic Alterations In Low-and High-grade Extranodal Marginamentioning
confidence: 99%
“…However, immunohistochemical expression analyses showed that AID is detectable only in a minority of the cases. 75,156 Accordingly, several investigators demonstrated variable, but generally low AID mRNA expression levels in MALT lymphomas. 156,162,163 On the other hand, in ~50% of DLBCL, several proto-oncogenes, including PIM1, PAX5, RhoH/TTF and cMYC are targeted by aberrant SHM.…”
Section: Genetic Alterations In Low-and High-grade Extranodal Marginamentioning
confidence: 99%
See 1 more Smart Citation